Correlation of Computed Tomography findings with Glasgow Coma Scale in patients with acute traumatic brain injury - Sah, SK; Subedi, ND; Poudel, K; Mallik, M (Journal of College of Medical Sciences-Nepal, 2015)
OBJECTIVE To correlate Computed Tomography (CT) findings with Glasgow Coma Scale (GCS) in patients with acute traumatic brain injury attending in Chitwan Medical College teaching hospital Chitwan, Nepal. MATERIALS AND METHODS A cross-sectional study was performed among 50 patients of acute (less than24 hours) cases of craniocerebral trauma over a period of four months. The patient’s level of consciousness (GCS) was determined and a brain CT scan without contrast media was performed. A sixth generation General Electric (GE) CT scan was utilized and 5mm and 10mm sections were obtained for infratentorial and supratentorial parts respectively. RESULT The age range of the patients was 1 to 75 years (mean age 35.6± 21.516 years) and male: female ratio was 3.1:1. The most common causes of head injury were road traffic accident (RTA) (60%), fall injury (20%), physical assault (12%) and pedestrian injuries (8%). The distribution of patients in accordance with consciousness level was found to be 54% with mild TBI (GCS score 12 to 14), 28% with moderate TBI (GCS score 11 to 8) and 18% with severe TBI (GCS score less than 7). The presence of mixed lesions and midline shift regardless of the underlying lesion on CT scan was accompanied by lower GCS. CONCLUSION The presence of mixed lesions and midline shift regardless of the underlying lesion on CT scan were accompanied with lower GCS. Patients having single lesion had more GCS level than mixed level and mid line shift type of injury. Journal of College of Medical Sciences-Nepal, 2014, Vol.10(2); 4-9